Pengaruh Kepemimpinan Orang Tua Terhadap Perilaku Beragama Siswa : The Influence of Parental Leadership on Students' Religious Behavior - Jahro, Nashihatud Diniyah; Farida, Farida (Thawalib: Jurnal Kependidikan Islam, 2024)
Students' religious behavior can be influenced by parental leadership style. When parents adopt an authoritarian leadership style, there may be a decrease in students' religious behavior. This research aims to describe the relationship between parental leadership style, students' religious behavior, and its impact. Conducted at Madrasah Tsanawiyah Al-Wathoniyah1A Duren Sawit, East Jakarta, this research employs a descriptive quantitative method with correlation statistical analysis. From a population of 203 students, a sample of 50 students was taken, using a questionnaire for data collection. The analysis results indicate that both parental leadership style and students' academic achievement fall into the good category. The results also show a significant influence between parental leadership style and students' religious behavior, with a correlation coefficient of 0.787, exceeding the critical value of 0.250 at a significance level of 0.01. The obtained R2 of 0.705 indicates that parental leadership style influences students' religious behavior by 70.5%.